Constitutive activation of LXR in macrophages regulates metabolic and inflammatory gene expression: identification of ARL7 as a direct target - Hong, Cynthia (The American Society for Biochemistry and Molecular Biology, 2011)
Ligand activation of liver X receptors (LXRs) has been shown to impact both lipid metabolism and inflammation. One complicating factor in studies utilizing synthetic LXR agonists is the potential for pharmacologic and receptor-independent effects. Here, we describe an LXR gain-of-function system that does not depend on the addition of exogenous ligand. We generated transgenic mice expressing a constitutively active VP16-LXRα protein from the aP2 promoter. These mice exhibit increased LXR signaling selectively in adipose and macrophages. Analysis of gene expression in primary macrophages derived from two independent VP16-LXRα transgenic lines confirmed the ability of LXR to drive expression of genes involved in cholesterol efflux and fatty acid synthesis. Moreover, VP16-LXRα expression also suppressed the induction of inflammatory genes by lipopolysaccharide to a comparable degree as synthetic agonist. We further utilized VP16-LXRα-expressing macrophages to identify and validate new targets for LXRs, including the gene encoding ADP-ribosylation factor-like 7 (ARL7). ARL7 has previously been shown to transport cholesterol to the membrane for ABCA1-associated removal and thus may be integral to the LXR-dependent efflux pathway. We show that the ARL7 promoter contains a functional LXRE and can be transactivated by LXRs in a sequence-specific manner, indicating that ARL7 is a direct target of LXR. These findings provide further support for an important role of LXRs in the coordinated regulation of lipid metabolic and inflammatory gene programs in macrophages.